2014
DOI: 10.1017/s0007114514000543
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake, growth rate and body composition of young Labrador Retrievers and Miniature Schnauzers fed different dietary levels of vitamin A

Abstract: Research in rodents has shown that dietary vitamin A reduces body fat by enhancing fat mobilisation and energy utilisation; however, their effects in growing dogs remain unclear. In the present study, we evaluated the development of body weight and body composition and compared observed energy intake with predicted energy intake in forty-nine puppies from two breeds (twenty-four Labrador Retriever (LAB) and twenty-five Miniature Schnauzer (MS)). A total of four different diets with increasing vitamin A content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…When the energy requirements of the Yorkshire terriers, Labrador retrievers and miniature Schnauzers were compared, breed-specific patterns were observed. In agreement with data previously reported for miniature Schnauzer puppies ( 8 ) , Yorkshire terrier puppies required lower energy intake to maintain ideal body condition score than did Labrador retriever puppies until 23 weeks of age. The energy intakes of the miniature Schnauzer puppies were very similar to those of the Yorkshire terriers until 16 weeks of age when they diverged, possibly due to a longer rapid growth phase in the miniature Schnauzers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When the energy requirements of the Yorkshire terriers, Labrador retrievers and miniature Schnauzers were compared, breed-specific patterns were observed. In agreement with data previously reported for miniature Schnauzer puppies ( 8 ) , Yorkshire terrier puppies required lower energy intake to maintain ideal body condition score than did Labrador retriever puppies until 23 weeks of age. The energy intakes of the miniature Schnauzer puppies were very similar to those of the Yorkshire terriers until 16 weeks of age when they diverged, possibly due to a longer rapid growth phase in the miniature Schnauzers.…”
Section: Discussionsupporting
confidence: 92%
“…1) was overestimated by the NRC (2006) ( 9 ) equation from 10 to 20 weeks of age whilst the values were comparable from 21 to 52 weeks of age with the exception of weeks 25 and 45. When compared with the energy requirement values reported by Brenten et al ( 8 ) (Fig. 2), there was a significant interaction of breed with time ( P  < 0·0001) with the energy intake of Yorkshire terriers being significantly less than that of Labrador retrievers from 10 to 29 weeks of age ( P  ≤ 0·05) by 77·4 (95 % CI 132·6, 61·1) to 376·6 (95 % CI 477·4, 275·3) kJ/kg 0·75 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, unlike the WHO growth standards, it is unlikely that a single growth standard could be created that could be applied to all dogs. Furthermore, whilst previous studies have reported how bodyweight changes during the growth phase for a small number of breeds [ 10 , 11 , 12 , 13 , 14 ], such data are not sufficient for creation of growth curves for all breeds and sizes.…”
Section: Introductionmentioning
confidence: 98%
“…For MCV and MCH a significant effect of breed was observed with miniature schnauzers having significantly higher MCV and MCH throughout the trial. It can be speculated whether the smaller RBC size in labrador retriever presents an adaptation to the higher metabolic rate ( Brenten and others 2014 ) providing an increased surface area for oxygen exchange ( Hawkey 1975 ).…”
Section: Discussionmentioning
confidence: 99%